دراسة فاعلية برنامج LSVT LOUDالعلاجي في تحسين شدة الصوت لدى ذوي الاضطرابات العصبية -دراسة ميدانية بعيادات أرطفونية بمدينة الأغواط - حميدة أية جيهان لبقع; سعاد ابراهيمي (My University, 2022)
The present study aimed to verify the effectiveness of the LSVT LOUD treatment method in improving the intensity of the voice in people with neurological disorders. It is consisted of three cases with vocal disorders of neurological origin, namely, Parkinson’s case, Broca’s aphasia, and Ziemssen syndrome. The researcher, therefore, relied on the experimental approach and a quasi-experimental with a single-group design. She, also, used the LSVT LOUD treatment method, and the Praat program for pre and post measurement The results of the study, hence, proved the effectiveness of the LSVT LOUD treatment method in improving the intensity of the voice in people with neurological disordersLSVT LOUD Therapeutic method, Intensity of Voice, Neurological Disorders, Praat Program.